2008
DOI: 10.1002/aqc.968
|View full text |Cite
|
Sign up to set email alerts
|

Establishing survey and monitoring protocols for the assessment of conservation status of fish populations in river Special Areas of Conservation in the UK

Abstract: ABSTRACT1. Under the EC Habitats Directive (92/43/EEC), several rivers in the UK have been designated Special Areas of Conservation (SACs) because they support important populations of fish species. Several factors need to be considered when establishing survey protocols to assess the conservation status of fish species in these rivers.2. It is important to understand the biology and habitat requirements of fish species and to design appropriate monitoring surveys that adequately assess the status of the fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 12 publications
0
42
0
1
Order By: Relevance
“…Appreciable differences in bullhead abundance from site to site were also found in the Garonne stream system (Legalle et al, 2005). In those parts of northern Europe in which bullhead populations are not threatened and the species is quite common or even abundant, abundances of less than 0.2 individuals·m -2 and 0.5 individuals·m -2 for upland rivers and lowland rivers respectively indicate sites with unfavourable conditions (Copp et al, 1994;Carter et al, 2004;Cowx and Harvey, 2003;Cowx et al, 2009). There are several possible reasons for the relatively low abundance of C. haemusi in the river Vit tributaries.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Appreciable differences in bullhead abundance from site to site were also found in the Garonne stream system (Legalle et al, 2005). In those parts of northern Europe in which bullhead populations are not threatened and the species is quite common or even abundant, abundances of less than 0.2 individuals·m -2 and 0.5 individuals·m -2 for upland rivers and lowland rivers respectively indicate sites with unfavourable conditions (Copp et al, 1994;Carter et al, 2004;Cowx and Harvey, 2003;Cowx et al, 2009). There are several possible reasons for the relatively low abundance of C. haemusi in the river Vit tributaries.…”
Section: Discussionmentioning
confidence: 97%
“…The present assessment of the population status of C. haemusi was based on three main criteria: population demographic structure, abundance and species distribution as recommended by Cowx and Harvey (2003) and Cowx et al (2009). The data from the length frequency analysis suggested that the investigated Vit sculpin populations contained more than three age classes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, populations in many areas are likely to have been underestimated. Specific surveys may therefore be required to quantify the status of target populations before passage improvements are undertaken (Cowx et al 2009;Moser et al 2007), and surveys of passage efficiency and habitat quality will also reduce the subjectivity of the assessment (Kemp and O'Hanley 2010;Raven et al 1998). Indeed, the greatest sources of between-assessor differences in B were generally the estimates of F and P. It may also be possible to incorporate confidence rankings for estimates based upon expert judgement, as is being developed for risk assessment of non-native species (e.g.…”
Section: Discussionmentioning
confidence: 99%